Medical futility: a major ethical issue in end of life care: an outlook from medical and Islamic legal rulings - Che Mohamad, Che Anuar; Mohd Azaman, Faizatul Najihah; Abdul Ghani, Muhamad Rasydan; Abdul Rahim, Mohamad Shahrir; Md Tahir, Mohd Faiz; Shahar, Mohammad Arif; Hashi, Abdurezak Abdulahi; Mohamad, Hasbullah; Ismail, Mohd Nizamuddin; Nanyan, Suhaila; Roslan, Rosazra; Azmi, Ahmad Najib; et al. (2019)
Aims / Background: The ethical issues surrounding end of life care are recent subjects of heated discussions. While issues like brain death has been thoroughly deliberated and well responded by Islamic authorities; some remain far from certainty and requires further exploration. This study aimed to identify various clinical situations with ethical implications related to selected major issues in end of life care followed by in-depth analysis on the medical aspects and Islamic legal rulings.